The Political Ecology of Urban Expansion and Air Pollution in Kathmandu - Acharya, Abinav (Journal of Development Review, 2024)
This study analyzes the relationship between rapid urbanization, political priorities, and air quality issues in Kathmandu city of Nepal, aiming to identify sustainable urban planning solutions. Utilizing secondary data sources, such as governmental reports, environmental studies, and urban development records, the research employs a mixed-methods approach to analyze the factors driving urban expansion and their impact on air pollution. Key variables measured include population density, urban growth rate, traffic volume, industrial activity, and green space availability. The findings reveal that unregulated urban growth, driven by economic and infrastructural priorities, significantly contributes to deteriorating air quality. Political decisions often prioritize development over environmental protection, leading to insufficient enforcement of pollution control measures. Critical gaps in urban planning policies, such as the lack of green spaces and weak regulatory frameworks for industrial emissions, are identified. To address these issues, the study suggests implementing stricter air quality regulations, promoting green infrastructure, and enhancing public transportation systems. It recommends increasing inter-agency collaboration to integrate environmental considerations into urban development plans and engaging local communities in environmental decision-making processes. The research concludes that balancing development goals with environmental sustainability is essential for mitigating pollution and promoting healthier urban living conditions in Kathmandu.